Baicalin Attenuates Subarachnoid Hemorrhagic Brain Injury by Modulating Blood-Brain Barrier Disruption, Inflammation, and Oxidative Damage in Mice. (24th August 2017) - Shi, Xianqing; Fu, Yongjian; Zhang, SongSong; Ding, Hao; Chen, Jin
Abstract : In subarachnoid hemorrhagic brain injury, the early crucial events are edema formation due to inflammatory responses and blood-brain barrier disruption. Baicalin, a flavone glycoside, has antineuroinflammatory and antioxidant properties. We examined the effect of baicalin in subarachnoid hemorrhagic brain injury. Subarachnoid hemorrhage was induced through filament perforation and either baicalin or vehicle was administered 30 min prior to surgery. Brain tissues were collected 24 hours after surgery after evaluation of neurological scores. Brain tissues were processed for water content, real-time PCR, and immunoblot analyses. Baicalin improved neurological score and brain water content. Decreased levels of tight junction proteins (occludin, claudin-5, ZO-1, and collagen IV) required for blood-brain barrier function were restored to normal level by baicalin. Real-time PCR data demonstrated that baicalin attenuated increased proinflammatory cytokine (IL-1 β, IL-6, and CXCL-3) production in subarachnoid hemorrhage mice. In addition to that, baicalin attenuated microglial cell secretion of IL-1 β and IL-6 induced by lipopolysaccharide (100 ng/ml) dose dependently. Finally, baicalin attenuated induction of NOS-2 and NOX-2 in SAH mice at the mRNA and protein level. Thus, we demonstrated that baicalin inhibited microglial cell activation and reduced inflammation, oxidative damage, and brain edema.